An investigation of difficulties in information management for delay and disruption claims. Issue 5 (1st November 2022) - Ali, B; Aibinu, A A; Paton-Cole, V
Abstract: Information is important for making successful delay and disruption claims in construction projects. Without the required and complete information, it becomes challenging to provide supporting evidence for the damages incurred due to various delay and disruption events. However, there are several difficulties associated with managing the information needed for delay and disruption claims, which create complexities in the substantiation and resolution of these claims. This research, therefore, aims to explore such difficulties and propose recommendations for its mitigation to improve the process of delay and disruption claims. To achieve this, the concept of information management was adopted. Based on systematic review of literature using well-recognized databases (SCOPUS and Web of Sciences) and following PRISMA guidelines, 26 different difficulties were identified and prioritised in the collection, storage, access, and use of information required for delay and disruption claims. Incomplete information, lack of human resources, poor communication, verbal instructions and inaccuracy in recorded information were found to be the most common difficulties in the information management for delay and disruption claims. Recommendations are given to overcome the identified difficulties through available modern digital technologies such as drones, the internet of things, BIM, blockchain, bigdata and machine learning etc. This will pave way to obtain complete and accurate contemporaneous information on delays and disruptions in construction projects. Moreover, effective information management for delay and disruption claims will not only improve the process but also help in avoiding and/or amicably resolving disputes between contracting parties.